Managing Brain Extracellular K+ during Neuronal Activity: The Physiological Role of the Na+/K+-ATPase Subunit Isoforms - Larsen, Brian Roland; Stoica, Anca; MacAulay, Nanna (Frontiers in Physiology, 2016)
Abstract During neuronal activity in the brain, extracellular K+ rises and is subsequently removed to prevent a widespread depolarization. One of the key players in regulating extracellular K+ is the Na+/K+-ATPase, although the relative involvement and physiological impact of the different subunit isoform compositions of the Na+/K+-ATPase remain unresolved. The various cell types in the brain serve a certain temporal contribution in the face of network activity; astrocytes respond directly to the immediate release of K+ from neurons, whereas the neurons themselves become the primary K+ absorbers as activity ends. The kinetic characteristics of the catalytic α subunit isoforms of the Na+/K+-ATPase are, partly, determined by the accessory β subunit with which they combine. The isoform combinations expressed by astrocytes and neurons, respectively, appear to be in line with the kinetic characteristics required to fulfill their distinct physiological roles in clearance of K+ from the extracellular space in the face of neuronal activity. Understanding the nature, impact and effects of the various Na+/K+-ATPase isoform combinations in K+ management in the central nervous system might reveal insights into pathological conditions such as epilepsy, migraine, and spreading depolarization following cerebral ischemia. In addition, particular neurological diseases occur as a result of mutations in the α2- (familial hemiplegic migraine type 2) and α3 isoforms (rapid-onset dystonia parkinsonism/alternating hemiplegia of childhood). This review addresses aspects of the Na+/K+-ATPase in the regulation of extracellular K+ in the central nervous system as well as the related pathophysiology. Understanding the physiological setting in non-pathological tissue would provide a better understanding of the pathological events occurring during disease.